Transtemporal Venous Decompression for Idiopathic Venous Pulsatile Tinnitus - Slater, Patrick; Korla, Neha; Slater, Caroline (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective To evaluate the clinical characteristics and present surgical outcomes of transtemporal venous decompression technique in the treatment of pulsatile tinnitus (PT).Study Design This is a prospective cohort study.Setting This study was done at the tertiary private neurotologic skull base clinic.Participants The primary author, between March 2012 and February 2013, evaluated 55 patients with the complaint of PT. Seven out of the 55 patients were diagnosed with severe, unrelenting idiopathic pulsatile tinnitus (IPT), and were placed into the study. These seven patients had temporal bone computed tomography, magnetic resonance imaging, arteriogram, videonystagmography, electrocochleography, and lumbar puncture based on the symptoms. All the seven patients underwent transtemporal venous decompression surgery.Main Outcome Measure Resolution of PT was determined as the primary outcome measure.Results Six out of seven patients had complete resolution of their PT immediately after surgery and at 3 to 4 years follow-up. One patient developed intracranial hypertension after 3 months requiring ventriculoperitoneal shunt, which resolved PT as well. No complications occurred.Conclusion A significant subset of the PT patient population has known reversible causes. The more common includes conductive hearing loss, superior canal dehiscence, benign intracranial hypertension, jugulosigmoid venous anomalies, stapedial myoclonus, etc. There exists a subset of patients who have IPT. Transtemporal venous decompression is a surgical technique that can be employed to give patients with IPT long-term relief.
Keywords: tinnitus; pulsatile tinnitus; sigmoid sinus; jugular bulb; intracranial; hypertension; turbulent flow of blood; venous decompression